2017
DOI: 10.1016/j.cag.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of multi-exposure HDR image deghosting methods

Abstract: To avoid motion artefacts when merging multiple exposures into a high dynamic range image, a number of HDR deghosting algorithms have been proposed. However, these algorithms do not work equally well on all types of scenes, and some may even introduce additional artefacts. As the number of proposed deghosting methods is increasing rapidly, there is an immediate need to evaluate them and compare their results. Even though subjective methods of evaluation provide reliable means of testing, they are often cumbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In order to evaluate HDR images, several image quality metrics have been developed and adapted to the HDR domain. These include puPSNR [29], puSSIM [30] and HDR-VDP-2 [31], which have been adopted for comparing HDR images for a number of applications [32], [33] [35]. These metrics are capable of addressing a wide range luminance and are used widely.…”
Section: B Bld Algorithms Evaluationmentioning
confidence: 99%
“…In order to evaluate HDR images, several image quality metrics have been developed and adapted to the HDR domain. These include puPSNR [29], puSSIM [30] and HDR-VDP-2 [31], which have been adopted for comparing HDR images for a number of applications [32], [33] [35]. These metrics are capable of addressing a wide range luminance and are used widely.…”
Section: B Bld Algorithms Evaluationmentioning
confidence: 99%
“…This set is an important source of near-threshold distortions. deghosting (12 images) contains artifacts due to HDR merging, which exposes shortcomings of popular deghosting methods [Karađuzović-Hadžiabdić et al 2017]. ibr (36 images), and cgibr (6 images) contain artifacts produced by viewinterpolation and image-based rendering methods, which come from [Adhikarla et al 2017].…”
Section: Stimulimentioning
confidence: 99%
“…For example, Tursun et al [45] conducted a user study to examine HDR quality and found that the methods of Sen et al [39] and Hu et al [19] ranked first and second, respectively, with a sizeable margin over other state-of-the-art methods. More recently, Karaduzovic-Hadziabdic et al [25] also found that the method of Sen et al [39] outperformed others for most scenes. Finally, while most algorithms require that the image stack be captured only by varying the exposure time between images (changing settings like the aperture affects the depth-of-field, which makes images difficult to align or deghost), Sen et al [39] showed that their patchbased method is able to handle changes in depth-of-field automatically, thereby enabling longer exposures than could be done by simply changing the exposure time.…”
Section: Discussionmentioning
confidence: 92%